Ethnographic Gayo Community Of Tampur Paloh Village In The Lower Tamiang River, Simpang Jernih District, East Aceh Regency, Aceh Province: Etnografi Masyarakat Gayo Desa Tampur Paloh Di Hilir Sungai Tamiang, Kecamatan Simpang Jernih, Kabupaten Aceh Timur, Provinsi Aceh - Muhammad Farhan Zuldiansyah; Zuska, Fikarwin (Progress In Social Development, 2022)
ABSTRACT: Formal education in Tampur Paloh Village is lagging in all aspects, especially in the field of communication and the feasibility of facilities and support. This is the main problem of formal education there which leads to the low competitiveness of local children in the regional and even national arena. This study will discuss the situation and backwardness of rural communities downstream of the Tamiang River, Simpang Jernih District, East Aceh Regency, Aceh Province by looking at the dynamics that occur in formal schools. This research was conducted using qualitative descriptive methods with data sourced from participatory observations in the region. Explain clearly the facts on the ground and to what extent they lag behind the relevance of today's education. By being exposed to the limitations of formal schools, the local community can invite further steps to address the limitations of the quality of these formal studies. ABSTRAK: Pendidikan Formal di Desa Tampur Paloh mengalami ketertinggalan dari segala aspek, khususnya di bidang komunikasi dan kelayakan sarana dan penunjang. Hal tersebut menjadi masalah utama pendidikan formal disana yang berujung menjadi rendahnya daya saing anak setempat di kancah daerah bahkan nasional. Kajian ini akan membahas keadaan dan ketertinggalan masyarakat pedalaman di Hilir Sungai Tamiang, Kecamatan Simpang Jernih, Kabupaten Aceh Timur, Provinsi Aceh dengan melihat dinamika yang terjadi di sekolah formal. Penelitian ini dilakukan dengan menggunakan metode deskriptif kualitatif dengan data yang bersumber dari observasi partisipatif di wilayah tersebut. Menjabarkan dengan jelas fakta di lapangan dan sampai sejauh apa ketertinggalan mereka terhadap kerelavan pendidikan zaman sekarang. Dengan tereksposnya keterbatasan sekolah formal masyarakat setempat dapat mengundang langkah lanjutan penanganan keterbatasan kualitas studi formal tersebut.